The Effect of Stress-Playing Style Exercises on the Development of Some Biomotor Abilities of Young Football Players - Qasim Muhammad Ali Hazim; Ahmed Abdulameer Hamzah (Indian Journal of Forensic Medicine & Toxicology, 2021)
The football game has witnessed a great development in terms of the speed of play, possession and pressureon the ball carrier. Those involved in the game have to keep pace with this development through the useof integrated training programs that contain basic and advanced exercises that take care of most detailsof the game in addition to paying attention to the physical and movement that the player needs duringthe performance, such as Strength, speed, endurance, flexibility, ability, agility, coordination. and whatis associated with it, especially during defensive or offensive football performance, which contributes tocontrolling the course of the game. The importance of the research is that it is a research attempt that isconcerned with consolidating the idea of a stress playing style in the reality of Iraqi clubs and teams trainingthrough this defensive method to achieve the desired goal, as well as experimenting with the use of defensiveexercises characterized by rapid application and high accuracy together, and to know the extent of the impactof exercises in the style of compressive play on the development of some biomechanical capabilities of youngfootball players in a step aimed at strengthening the sports field with practical experiments and service toresearchers in the sports field. The research aims to identify the impact of exercises with a stress playing styleon the development of some biomechanical capabilities of young football players. The researchers identifiedthe research community, who are the (23) players of the Al-shuohda football Club, and the research samplewas chosen by a random method (lottery) of (10) players, appropriate statistical means were used to finddifferences in the pre and post-tests. The researchers came out with the following conclusions: Compressiveplay style exercises developed some biomechanical capabilities (movement speed, agility and compatibility)for the experimental group under discussion, compressive play exercises simulated the player for the sameconditions of the match.